Radical climate policies - van der Ploeg, F; Venables, AJ (University of Oxford, 2022)
In the presence of strategic complementarities stemming from peer effects in demand or from technological spill-overs, propagation and amplification mechanisms increase the effectiveness of climate policies. This suggests that climate goals can be met with smaller policy interventions. However, if there are multiple equilibria, radical and more ambitious climate policies are needed to shift the economy from a high-emissions to a low-emissions path.. Once the radical shift has taken place the transformative policies can be withdrawn. More generally, such policies can set in motion social, technological, and political tipping points. The rationale for such policies is strengthened due to key households, corporations and institutions being at the centre of networks, and thus radical climate policies should identify those agents and leverage them. Our proposals offer a complementary perspective to scholars that have emphasised insights from the literature on early warning signals to advocate sensitive intervention points to get more effective and more transformative climate policies.